Ornamental Fish Diversity in Some Selected Water Bodies of the Upper Brahmaputra Basin in Assam, India - Deb, Shatabdi; Sonowal, Jyotirmoy; Biswas, Shyama Prasad (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The northeastern region of India is renowned for its rich repository of ornamental fish. Though the majority of them constitute a rich source of dietary protein, many of them are also sourced as ornamental fish from the region. Among different states in the region, Assam is blessed with a huge repository of ornamental fish resources that are found to occur naturally in a variety of freshwater habitats. The present investigation deals with the diversity of ornamental fishes in prominent fish assemblage areas of the state. A total of 49 ornamental fish species were recorded represented by 32 genera under 18 families and 8 orders from the studied water bodies. Among the water bodies, R. Dibru accounted for the highest number of species, i.e. 46 ornamental fishes belonging to 31genera under 18 families. Mer Beel and R. Burhidihing recorded the lowest number of species. The findings of the present investigation provide crucial information on diversity in the study area, which would be helpful in better management and conservation of ornamental fish in the region.